2017
DOI: 10.3390/vetsci4040057
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Third Generation Cephalosporin Resistant Escherichia coli from Dairy Cow Manure

Abstract: The production of extended-spectrum β-lactamases (ESBLs) conferring resistance to new derivatives of β-lactams is a major public health threat if present in pathogenic Gram-negative bacteria. The objective of this study was to characterize ceftiofur (TIO)- or cefotaxime (FOX)-resistant Escherichia coli isolated from dairy cow manure. Twenty-four manure samples were collected from four farms and incubated under anaerobic conditions for 20 weeks at 4 °C or at 25 °C. A total of 37 TIO- or F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…Some studies have shown that ESBL are responsible for producing antibiotic-resistant bacteria strains [11,12]. The spread of the strains is likely to limit the effectiveness of antimicrobials used to treat the patients suffering from pathogen bacteria such as Escherichiacoli and Salmonella [13][14][15][16] These ESBL-producing bacteria often show resistance to several antimicrobials such as third and fourth generation cephalosporins as well as quinolones and aminoglycosides [17][18][19]. Although inhibited by clavulanic acid, ESBL enzymes have the ability to hydrolyze third generation cephalosporins and aztreonam [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that ESBL are responsible for producing antibiotic-resistant bacteria strains [11,12]. The spread of the strains is likely to limit the effectiveness of antimicrobials used to treat the patients suffering from pathogen bacteria such as Escherichiacoli and Salmonella [13][14][15][16] These ESBL-producing bacteria often show resistance to several antimicrobials such as third and fourth generation cephalosporins as well as quinolones and aminoglycosides [17][18][19]. Although inhibited by clavulanic acid, ESBL enzymes have the ability to hydrolyze third generation cephalosporins and aztreonam [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found a bla CMY-2 gene flanked by the IncI1 plasmid marker in one of our isolates. This plasmid-mediated ampC gene was also observed on IncFIB, IncI1, IncA/C, IncF, and IncK/B in E. coli isolates from recreational beaches and private drinking water in Canada (Hopkins et al, 2006;Mulvey et al, 2009;Martin et al, 2012;Rehman et al, 2017). The presence of plasmid Inc groups in the aquatic environment may play a role in maintenance and dissemination of resistance genes between environment, animals and humans.…”
Section: Discussionmentioning
confidence: 76%
“…A maximum likelihood tree was generated based on SNPs alignment (Kaas et al, 2014). SEED Viewer (SEED, 2018) was used to visualize whole genome sequence comparisons of coding sequence identity between reference strains and isolates from this study (Overbeek et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…Infections caused by extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae have been linked to their dissemination through both food and the environment [1][2][3]. ESBL-producing bacteria, including E. coli are frequently resistant to multiple antimicrobials including 3rd and 4th generation cephalosporins in addition to quinolones and aminoglycosides [1,2,4]. These bacteria have been designated priority group 1 pathogens for the development of alternative antimicrobial therapies by the World Health Organization [5] as they can cause serious urinary tract [6,7] and bloodstream [8][9][10] infections, occasionally resulting in mortalities [11].…”
Section: Introductionmentioning
confidence: 99%